PERSEPSI BODY IMAGE PADA REMAJA PUTRI UNDERWEIGHT DAN OVERWEIGHT USIA 16-18 TAHUN DI KOTA TANGERANG 2020 - Marissa Febriani Lumbantoruan (2020)
Perceptions and views of adolescent girls about body image are closely related to body shape dissatisfaction, which in turn affects of eating patterns and eating disorders in adolescents. Both overweight and underweight, they have different perceptions and views about their body shape and appearance. This study aims to explore the perception of body image in underweight and overweight in adolescents girls aged 16-18 years in Tangerang. In-depth interviews were conducted on 5 underweight teenage girls and 5 overweight teenage girls with a case study approach with 4 (four) domain items, namely the concept of body image, body shape & ideal perception, efforts for achieving the ideal body composition shape, and eating habits of adolescent girls. The results showed that 5 overweight teenage girls had dissatisfaction with their body shape and 2 out of 5 underweight teenage girls felt less satisfied with their body shape. Keywords: Body Image perceptions, Body Image Dissatisfaction, Eating Pattern